Honduras publications in the Science Citation Index Expanded: institutions, fields and authors - Monge-Nájera, Julián; Ho, Yuh-Shan (Revista de Biología Tropical, 2017)
Honduras is the second largest country in Central America, but 63 % of its population lives in poverty and it is the Central American country with less scientific journals. Even though Honduras has been included in general studies about Latin American science, there are no specific bibliometric studies about the productivity of the country, so this is the first formal study about the most productive institutions, fields and authors in Honduras. The Science Citation Index Expanded (SCI-EXPANDED), Web of Science Core Collection was used to collect the bibliographic data. There are no Honduras publications from 1903 to 1972 in SCI-EXPANDED. Honduras publications from 1973 to 2015 were further analyzed. A total of 1 146 Honduras publications with 13 document types in the Science Citation Index Expanded from 1973 to 2015 were found. Nearly 95 % of the articles in the database are in English, suggesting that articles in this language have the greatest visibility in the database, similar to other Central American countries. The countries with which Honduras publishes (e.g. Mexico, other Central American countries) follow the geographic and cultural affinity model, i.e. researchers tend to collaborate with colleagues that have similar culture or that are geographically close. This pattern has been found for other Central American countries. The focus of Honduran scientists in health and agriculture problems is typical on the less developed countries; on this respect Honduras is more similar to its closest neighbor, Nicaragua, than to smaller but more developed Central American countries like Panama and Costa Rica. Overall, the situation of scientific research and output in Honduras is improving, with more articles and citation in the SCI-EXPANDED, and this positive trend should bring about benefits for the people of Honduras.